2022
DOI: 10.1080/08995605.2021.1989236
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive performance, fatigue, emotional, and physiological strains in simulated long-duration flight missions

Abstract: Pilots in long-duration flight missions in single-seat aircraft may be affected by fatigue. This study determined associations between cognitive performance, emotions and physiological activation and deactivation – measured by heart rate variability (HRV) – in a simulated 11-h flight mission in the 39 Gripen aircraft. Twelve participants volunteered for the study. Perceived fatigue was measured by the Samn-Perelli Fatigue Index (SPFI). Cognitive performance was measured by non-executive and executive tasks. Em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 46 publications
0
0
1
Order By: Relevance
“…The trends in physiological parameters were consistent with previous studies [ 54 , 55 , 56 , 57 , 58 ]. Nevertheless, the results showed slight differences in ULF compared to some studies [ 9 , 59 , 60 , 61 , 62 ] which believed that ULF cannot reflect a human’s workload level. After further literature research and analysis, our results were found to be justified.…”
Section: Resultscontrasting
confidence: 74%
“…The trends in physiological parameters were consistent with previous studies [ 54 , 55 , 56 , 57 , 58 ]. Nevertheless, the results showed slight differences in ULF compared to some studies [ 9 , 59 , 60 , 61 , 62 ] which believed that ULF cannot reflect a human’s workload level. After further literature research and analysis, our results were found to be justified.…”
Section: Resultscontrasting
confidence: 74%
“…The effects of fatigue on abilities during work could be analyzed according to the analysis results. Compared with the previous research [1,14], this study showed the effect of fatigue on abilities with new indicators. All the research revealed the adverse effects of fatigue on ATCOs.…”
Section: Discussionmentioning
confidence: 66%
“…The effects of fatigue generally tend to be a continuum ranging from mild to severe and disabling manifestations such as exhaustion, overstrain, and chronic fatigue syndrome [13]. Under the influence of fatigue, people's alertness, motor skills, reflex ability, judgment, cognitive performance and decision-making will be impaired [1,14]. It has been proven that heart rate and heart rate variability were also highly correlated with fatigue [15,16].…”
Section: Literature Review Of the Studies On Fatigue In Atcosmentioning
confidence: 99%
“…Studies focusing on cognitive fatigue and mental workload in aviation have been conducted in flight simulators or during actual flight duties (McMahon & Newman, 2018;Wang et al, 2020;Rosa et al, 2022). However, the equipment must be able to sustain a G-force and fit in a confined space, the procedure during actual flight duties is extremely difficult and costinhibitive.…”
Section: Introductionmentioning
confidence: 99%